Retrieval of Images Using Data Mining Techniques - Rawat, Priyanka; Sethi, Shilpa (International Journal of Computer Sciences and Engineering, 2018)
This paper presents the Content Based Image Retrieval System .The Content Based Image retrieval (CBIR) is up-and-coming exploring area that deals with image retrieval using visual feature extraction, multidimensional indexing, and retrieval system design. Color, Texture and Shape information have been the primitive image descriptors in content based image retrieval systems. The goal is to retrieve the images from the database. Database contains lot of images which belongs to different categories. There are several methods to retrieve the images from large dataset, but they have some drawbacks. In this paper, techniques like clustering, association rules mining are used to mine the data. This paper also uses the fusion of multimodal features like visual and textual features. The proposed approach is simple and shows good results in term of efficiency.